Модель адміністративної юстиції в Україні та світі - Завальнюк, І. В.; Завальнюк, И. В.; Zaval'njuk, І. (My University, 2010)
The article presents the results of the features of creation and functioning of the bodies of administrative justice in Ukraine and in the World (on the example of Romano-Germanic legal family in the countries of Western Europe). It is analyzed the system of given bodies and their functions.
Завальнюк І. В. Модель адміністративної юстиції в Україні та світі / І. В. Завальнюк // Актуальні проблеми політики : зб. наук. пр. / редкол. : С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ ОЮА. - Одеса : Фенікс, 2010. - Вип. 40. - С. 79-84.
Keywords: модель адміністративної юстиції в Україні та світі; виникнення та функціонування органів адміністративної юстиції в Україні та країнах Східної Європи романо-німецької правової сім'ї; модель административной юстиции в Украине и мире; возникновение и функционирование органов административной юстиции в Украине и странах Западной Европы романо- германской правовой семьи; model of administrative justice in Ukraine and the world; he emergence and functioning of administrative justice in Ukraine and the countries of Western Europe Romano-Germanic legal family